Stance Expressions in Korean Students’ Writing in English - 이혜경 (담화와 인지, 2018)
Using an in-house non-native corpus and an established native corpus as data, this study strives to identify and compare the most frequently-used word sequences (i.e. lexical bundles) in the two corpora with reference to their structures and functions. In particular, this study pays its focused research attention to stance expressions culled from the two corpora qualitatively as well as quantitatively. It is acknowledged that Korean learners are less proficient in managing hedging epistemic expressions instrumental in the use of cautious language. Non-native writing further features more evaluative and stronger stances toward the propositional content. The study also suggests some pedagogical benefits of instructions about norms of academic writing and/or of recurrent exposures to the authentic uses of stance expressions.
Keywords: lexical bundles; BAWE; stance; modality; native vs. non-native